DOSENMENUMBUHKAN SIKAP MENCINTAI KEARIFAN LOKAL MELALUI PENGEMBANGAN BAHAN AJAR MATA KULIAH MENULIS KARYA ILMIAH UNTUK MAHASISWA PBSI TAHUN AKADEMIK 2014/2015 - Mukhlis .; Arisul Ulumuddin; Eva Ardiana I (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2015)
Instructional materials to write scientific papers in the Indonesian language and literature curriculum perluh developed based on the needs of students. In the development of teaching materials for students to write scientific papers should be adapted to the context of the students who have character values ?óÔé¼ÔÇ??óÔé¼ÔÇ?by integrating the values ?óÔé¼ÔÇ??óÔé¼ÔÇ?of character education. So that students not only get the Indonesian language and literature materials, but students gain experience that attitudes and provision of useful characters in his life. Character education can be loaded in the teaching materials is one of them is wisdom. In this study the development of teaching materials produced products to accommodate the needs of the teaching material to write scientific papers and the introduction of local wisdom. In the approach used in this study is research and development (R & D). The data sources of this study consisted of students and faculty. Product research results are validated by experts, limited tested. Keywords: teaching materials, scientific papers, character education